Acquired palmoplantar keratoderma associated with primary biliary cholangitis: Complete and persistent resolution after ursodeoxycholic acid treatment. (14th December 2021) - March‐Rodriguez, Alvaro; Marcantonio, Orianna; Olmos‐Alpiste, Ferran; Pujol, Ramon M.
Abstract: A 57‐year‐old woman presenting an acquired and persisting palmoplantar keratoderma associated with primary biliary cholangitis is reported. Treatment with oral ursodeoxycholic acid was prescribed, and a complete and persistent resolution of skin lesions was noted. This observation seems to support that acquired palmoplantar keratoderma is an uncommon cutaneous manifestation of primary biliary cholangitis.